Implementation of Communication in Increasing motivation for diversity based on an independent curriculum at the University in the Merdeka Student Exchange Program - Fatayan, Arum; Apoko, Tri Wintolo; Hendriana, Benny; Handayani, Isnaini; Irdalisa; Hanif, Isa Faqihuddin (Universitas Pendidikan Ganesha, 2025)
Indonesia has high cultural diversity, but this diversity often becomes a challenge in communication between individuals from different cultural backgrounds. Based on these problems, this study aims to analyze and improve students' diversity motivation by implementing the Independent Student Exchange Program (PMM) as part of universities' Independent Learning Independent Campus (MBKM) policy. This study uses a descriptive method with a quantitative approach. The subjects in this study were 103 PMM student participants from various universities in Indonesia. Data were collected through a questionnaire with an assessment scale to measure students' level of diversity motivation. The results of the data analysis showed that the PMM program succeeded in creating a significant cross-cultural learning experience, marked by an average questionnaire score of 95%. This program encourages students to respect cultural differences, strengthen a sense of unity, and foster an inclusive attitude. The conclusion of this study shows that the Independent Student Exchange Program effectively increases diversity motivation among students. The implications of this study underline the importance of integrating diversity values ​​in the independent curriculum to form adaptive and tolerant student characters in facing the challenges of the era of globalization and the Industrial Revolution 4.0.